Effect of the insecticides abamectin and lufenuron on eggs and larvae of Chrysoperla externa under laboratory conditions - Bueno, A. F.; Freitas, S. (Kluwer Academic Publ, 2004)
The side effects of two insecticides/acaricides, abamectin and lufenuron, on the eggs and larvae of Chrysoperla externa (Hagen) were studied in the laboratory (25 +/- 2degreesC, 62 +/- 10% RH and 12-h photophase). The analytical methods used were those proposed by the International Organization for Biological Control (IOBC)-Working Group for 'Pesticides and Beneficial Organisms'. Chrysoperla externa egg viability was not affected by abamectin. Neonate larvae from abamectin sprayed eggs as well as first, second and third instar larvae that were directly treated, developed normally and yielded normal adults. Lufenuron presented no adverse effects on egg survival. However, lufenuron induced high mortality in neonate larvae from treated eggs. These neonates, as well as lufenuron treated first and second instar larvae could not molt. In the third instar, high pupal mortality occurred. The results showed that abamectin is innocuous and that lufenurom is toxic to Chrysoperla externa eggs and larvae.
Keywords: Cítrus; chrysopidae; green lacewings; Insecticides; neuroptera; selectivity; side effects